Some Aspects of the Administrative Activity of Police in Road Traffic Safety - RAKHMET, Yerlan (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505//jarle.v9 3(33).37, 2018)
The article covers the research of the administrative activity of police for road traffic safety in the Republic of Kazakhstan and some foreign countries. Road traffic safety is one of the most important factors of the security of a state and a person. That’s why this sphere is so attractive for researchers. But one of its important constituents, that is, the administrative activity of police, has not been studied enough by now. The article aims at analysis of administrative and legal means used by police for road traffic safety in Kazakhstan and some foreign countries, their legislative consolidation, assessment of their efficiency and applicability of international practices within the national legal framework. The article studies the essence and directions of the administrative activity of police, international organizational and legal practices of police participation in road traffic safety, norms of the administrative legislation in Kazakhstan, conclusions and recommendations for future improvement of administrative measures applied for road traffic safety. Based on the study of administrative law standards and international practices in road traffic safety, the author offers areas to improve the administrative activity of police and its efficiency, and formulates proposals for future improvement of the administrative legislation in the Republic of Kazakhstan. Key clauses and conclusions of the article can be used in scientific and practical activities while studying road safety issues, comparing road traffic police laws in Kazakhstan and foreign countries, as well as in future reformation of the police law.